Strategi Recycle Air Limbah Domestik Terolah sebagai Penunjang Green Zone - Bonita Setyaningtias; Rizka Novembrianto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Industry 4.0 has brought significant changes to human life across various sectors, including education. The education sector serves as a fundamental pillar for the growth and development of future generations, requiring collaboration from all stakeholders. Effective regulations and measures are essential to improve the quality of education and teaching.One activity within the education sector generates domestic wastewater that must be treated. Domestic wastewater refers to water waste from household activities, such as washing, kitchen use, and toilets. This study employs a quantitative method using secondary data on wastewater flow rates and parameters. The research stages include preparation, data collection (both primary and secondary), data analysis, and the preparation of environmental documents.Domestic wastewater is categorized into grey water and black water. The treatment of wastewater using anaerobic and aerobic biofilters has proven effective in reducing organic pollutant levels. The treated wastewater will be repurposed for irrigating Green Zone in school buildings.